Deregulation of phytoene-β-carotene synthase results in derepression of astaxanthin synthesis at high glucose concentration in Phaffia rhodozyma astaxanthin-overproducing strain MK19 - Lili Miao (BMC Microbiology, 2019)
Abstract Background A major obstacle to industrial-scale astaxanthin production by the yeast Phaffia rhodozyma is the strong inhibitory effect of high glucose concentration on astaxanthin synthesis. We investigated, for the first time, the mechanism of the regulatory effect of high glucose (> 100 g/L) at the metabolite and transcription levels. Results Total carotenoid, β-carotene, and astaxanthin contents were greatly reduced in wild-type JCM9042 at high (110 g/L) glucose; in particular, β-carotene content at 24–72 h was only 14–17% of that at low (40 g/L) glucose. The inhibitory effect of high glucose on astaxanthin synthesis appeared to be due mainly to repression of lycopene-to-β-carotene and β-carotene-to-astaxanthin steps in the pathway. Expression of carotenogenic genes crtE, pbs, and ast was also strongly inhibited by high glucose; such inhibition was mediated by creA, a global negative regulator of carotenogenic genes which is strongly induced by glucose. In contrast, astaxanthin-overproducing, glucose metabolic derepression mutant strain MK19 displayed de-inhibition of astaxanthin synthesis at 110 g/L glucose; this de-inhibition was due mainly to deregulation of pbs and ast expression, which in turn resulted from low creA expression. Failure of glucose to induce the genes reg1 and hxk2, which maintain CreA activity, also accounts for the fact that astaxanthin synthesis in MK19 was not repressed at high glucose. Conclusion We conclude that astaxanthin synthesis in MK19 at high glucose is enhanced primarily through derepression of carotenogenic genes (particularly pbs), and that this process is mediated by CreA, Reg1, and Hxk2 in the glucose signaling pathway.